2023
DOI: 10.1001/jamanetworkopen.2023.4529
|View full text |Cite
|
Sign up to set email alerts
|

Plan Selection, Enrollee Risk, and Health Spending on the Patient Protection and Affordable Care Act Individual Marketplaces, 2019

Abstract: ImportanceThe Patient Protection and Affordable Care Act (ACA) individual marketplaces are a source of insurance for millions of residents in the US. However, the association between enrollee risk, health spending, and metal tier selection remains unclear.ObjectivesTo describe individual marketplace enrollees’ metal tier selections by risk score and assess enrollees’ health spending by metal tier, risk score, and spending type.Design, Setting, and ParticipantsThis retrospective, cross-sectional study analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…For example, mounting evidence, based on more limited claims data or simulation models, suggests that lowering the age of Medicare eligibility might increase nongroup premiums (Blue Cross Blue Shield Association, 2021; Eibner et al, 2019;Kotecki & Westrom, 2020), contrary to expectation before the ACA (Yamamoto, 2013). Moreover, prior research has found that nongroup enrollees tended to be at higher risk for medical spending compared with other private market enrollees yet spent less conditional on their risk score (Lissenden et al, 2020;Pelech & Stockley, 2022), and that, within the nongroup market, high-risk recipients of CSRs have relatively low spending (Treasure et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For example, mounting evidence, based on more limited claims data or simulation models, suggests that lowering the age of Medicare eligibility might increase nongroup premiums (Blue Cross Blue Shield Association, 2021; Eibner et al, 2019;Kotecki & Westrom, 2020), contrary to expectation before the ACA (Yamamoto, 2013). Moreover, prior research has found that nongroup enrollees tended to be at higher risk for medical spending compared with other private market enrollees yet spent less conditional on their risk score (Lissenden et al, 2020;Pelech & Stockley, 2022), and that, within the nongroup market, high-risk recipients of CSRs have relatively low spending (Treasure et al, 2023).…”
Section: Introductionmentioning
confidence: 99%